Smrtnost sov Strigiformes na avtocestah med Bologno in Trbižem (Italija) pozimi 1998-99 - Rubinič, Borut (Acrocephalus, 2000)
During the two inspections of three sections of the 278 km long Bologna-Monfalcone motorway in northern Italy on December 25th 1998 and March 8th 1999, the author found 70 cadavers of owls. 48 of these were identified, while in 36 of them the author also managed to determine their sex and age. For 25 individuals found on March 8th 1999, the surroundings of the place of recovery and the actual road location were established. The run over owls belonged to three different owl species: Long-eared Owl Asio otus, Little Owl Athene noctua and Barn Owl Tyto alba.
Keywords: bird; Birds; ptice; sove; Mortality; Ecosystem; mortaliteta; Transportation; Motor vehicles; Italy